Rethinking the sustainable development goals: Learning with and from community‐led initiatives - Hefrey, T.; Feola, G.; Penha‐Lopes, G.; Sekulova, F.; Esteves, A. (Sustainable Development, 2023)
This paper explores the actual and potential contributions of community‐led initiatives (CLIs) to the Sustainable Development Goals (SDGs). As examples of self‐determined practical action for sustainability and social justice, CLIs prefigure many of the intended outcomes of the SDGs. Existing evidence shows that CLIs are already contributing, at local scale, to almost all of the SDGs, and achieving particular success in bringing different goals into synergy. However, these achievements are based on ethics, guiding philosophies, issue framings, practical goals and ways of organising that differ significantly from those behind the formulation and delivery of the SDGs. Embracing those differences, and with them greater plurality and ongoing critical self‐reflection, would allow the SDGs to transcend certain self‐limiting contradictions, particularly concerning the role of economic growth. Such a shift in orientation is essential if the SDGs are to move from reinforcing to challenging the root causes of unsustainability and injustice.